Airport engineering : design, planning, and development of 21st century airports - Ashford, Norman; Mumayiz, Saleh A.; Wright, Paul H. (Hoboken, N.J. : Wiley, 2011)
First published in 1979, Airport Engineering by Ashford and Wright, has become a classic textbook in the education of airport engineers and transportation planners. Over the past twenty years, construction of new airports in the US has waned as construction abroad boomed. This trend resulted in the formation of the International Civil Aviation Organization (ICAO) which increasingly serves to codify civil aviation outside the US. This new edition if Airport Engineering will respond to this shift in the growth of airports globally, while still providing the best practices and tested fundamentals that have made the book successful for over 30 years.
Frontmatter -- The Structure and Organization of Air Transport -- Forecasting Air Transport Demand -- Characteristics of Aircraft As They Affect Airports -- Airport System Planning -- Airport Master Planning -- CNS/ATM -- Airport Capacity -- Airside Configuration and Geometric Design of the Airside -- Safeguarding the Airport -- Passenger Terminal -- Air Cargo Facilities -- Airport Drainage and Pavement Design -- Airport Access -- Heliports, STOLports, and Vertiports -- Airport Modeling and Simulation -- Airport City -- Environmental Impacts of Airports -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Airports -- Planning; Business; Engineering; TRANSPORTATION -- Aviation -- Commercial; TECHNOLOGY & ENGINEERING -- Aeronautics & Astronautics; Airports -- Planning; Llibres electrònics.; Electronic books